Analyses of the methodological differences between Muhaddithun and Usuliyyun in Hadith criticism - Ramle, Muhamad Rozaimi; Asni, Fathullah; Mohamad, Mohd Yusof (HRMARS, 2022)
This paper focuses on the difference in methodology between Muhaddithun and Usuliyyun on Hadith discourse. Hadith is commonly referred to as words, actions, and tacit approval of the prophet Muhammad ?. A muhaddith means someone who is highly knowledgeable and possesses mastery in the field of Hadith. An Usuliy on the other hand refers to scholars who have expertise on matters related to Usul al-Fiqh, namely the principle of Islamic jurisprudence. Differences of opinions between Muhaddithun and Usuliyyun are thought to have significant methodological variances in hadith criticism. Few modern scholars claimed the differences were absent since the Usuliyyun merely followed the Muhaddithun in matters of critics of Hadith. This opinion is nevertheless contrasted by other group scholars. Therefore, this study examined both paradigms on the methodological issues over the criticism of Hadith and analyzed their various views. For this purpose, analytical and critical methodologies were used in addition to the descriptive methodology. Classic books of sciences of Hadith such as Fath al-Mughith and the Muqaddimah ‘Ulum al-Hadith were analyzed for this purpose. As for Usul al-Fiqh, works like Raudat al-Na?ir and Nihayat al-Sul were scrutinized accordingly. This study demonstrated differences indeed existed between these two factions in matters related to criticism of hadith, both theoretically and practically.